2018
DOI: 10.3389/fnana.2018.00013
|View full text |Cite
|
Sign up to set email alerts
|

Neural Damage in Experimental Trypanosoma brucei gambiense Infection: Hypothalamic Peptidergic Sleep and Wake-Regulatory Neurons

Abstract: Neuron populations of the lateral hypothalamus which synthesize the orexin (OX)/hypocretin or melanin-concentrating hormone (MCH) peptides play crucial, reciprocal roles in regulating wake stability and sleep. The disease human African trypanosomiasis (HAT), also called sleeping sickness, caused by extracellular Trypanosoma brucei (T. b.) parasites, leads to characteristic sleep-wake cycle disruption and narcoleptic-like alterations of the sleep structure. Previous studies have revealed damage of OX and MCH ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Of note, the alterations we see in sleep behavior are distinct from the direct wake to REM transitions seen with narcolepsy that are mediated by the orexin system. While there is some indication that T. brucei infection causes orexin and MCH neuronal death in rats (Palomba et al, 2015) of which orexin loss would be expected to result in SOREMs, other studies have shown that only T. brucei gambiense induces significant damage to orexin and MCH neurons (Laperchia et al, 2018) as well as the SCN (Tesoriero et al, 2018) in susceptible organisms. However, these models may not fully recapitulate human sleeping sickness pathophysiology, as postmortem studies do not indicate significant neuronal damage (Kennedy, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the alterations we see in sleep behavior are distinct from the direct wake to REM transitions seen with narcolepsy that are mediated by the orexin system. While there is some indication that T. brucei infection causes orexin and MCH neuronal death in rats (Palomba et al, 2015) of which orexin loss would be expected to result in SOREMs, other studies have shown that only T. brucei gambiense induces significant damage to orexin and MCH neurons (Laperchia et al, 2018) as well as the SCN (Tesoriero et al, 2018) in susceptible organisms. However, these models may not fully recapitulate human sleeping sickness pathophysiology, as postmortem studies do not indicate significant neuronal damage (Kennedy, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Distinct sleep changes during T.b.b. infection can be due to altered function or damage of the population of neurons that reside in the lateral hypothalamus which releases the orexin peptide pair [55][56][57][58]. A role for T cells in narcolepsy, where sleep dysregulation resembles the one of T.b.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Autoptic analyses had shown diffuse microglial hyperplasia, a proliferation of astrocytes, and the formation of microglial nodules [13,14]. Studies carried on in experimental animal models proved astrocytosis and evidenced neuronal loss in some areas of the brain [15][16][17][18]. Another common feature between HAT patients and animal models is the presence of an inflammatory infiltrate in the parenchyma [19,20].…”
mentioning
confidence: 99%